Evaluasi Ciri Mekanis Dan Fisis Bioplastik Dari Campuran Poli (Asam Laktat) Dengan Polisakarida - Raffi Paramawati; Christofora Hanny Wijaya; Suminar Setiati Achmadi; Suliantari Suliantari (Jurnal Ilmu Pertanian Indonesia, 2007)
The study was aimed to evaluate physical and mechanical characteristics of blend of polylactic acid (PLA)and four types of polysaccharides, namely carrageenan, agar, tapioca, and garut starch. Agar and carrageenanshowed their ability to blend well with the PLA at a temperature of approximately 60ac, which was easilyobserved. Film sheets that were casted manually with better properties needed additives of triethanolamine oroleic acid, in terms of tensile strength, elastic modulus, and percent elongation at break which were categorizedas medium compared to other biodegradable plastics. Microstructure of the selected film revealed irregularformation of surface or amorphous, indicating that these films cannot be stored for a long period of time.